Methane emissions from natural gas and LNG imports: An increasingly urgent issue for the future of gas in Europe - Jonathan P. Stern (The Oxford Institute for Energy Studies, 2020)
Pressure is mounting on the natural gas and LNG community to reduce methane emissions and this is most urgent in EU countries following the adoption of much tougher greenhouse gas reduction targets of 2030 and the publication of the European Commission's Methane Strategy. With rapidly declining indigenous EU production and therefore rising import dependence, there are increasing calls for emissions from imported pipeline gas and LNG to be quantified and based on actual measurements, as opposed to standard emission factors. The Methane Strategy promises to be a significant milestone in that process. Companies which are supplying (or intending to supply) natural gas to the EU - the largest global import market for pipeline gas and a very significant market for LNG - would be well advised to pay close attention to how the regulation of methane emissions is unfolding, and to make an immediate and positive response. Failure to do so could accelerate the demise of natural gas in European energy balances faster than would otherwise have been the case, and shorten the time available for transition to decarbonised gases - specifically hydrogen - using existing natural gas infrastructure. This EU initiative will (and arguably already has) attracted attention from non-EU governments and companies involved in global gas and LNG trade. We have already seen deliveries of 'carbon neutral' LNG cargos to Asia, as well as a long-term LNG contract in which the greenhouse gas content of cargos will be measured, reported and verified (MRV) according to an agreed methodology. Natural gas and LNG exports, if based on these standards or those set out in the EU Methane Strategy, may be able to command premium prices from buyers eager to demonstrate their own GHG reduction credentials to governments, customers and civil society.
Keywords: 330; carbon-neutral; decarbonisation; Emissions; flaring; LNG; measurement; Methane; Natural gas; Reporting; super-emitter; venting; verification